2010
DOI: 10.1007/s10579-010-9118-8
|View full text |Cite
|
Sign up to set email alerts
|

The MATCH corpus: a corpus of older and younger users’ interactions with spoken dialogue systems

Abstract: We present the MATCH corpus, a unique data set of 447 dialogues in which 26 older and 24 younger adults interact with nine different spoken dialogue systems. The systems varied in the number of options presented and the confirmation strategy used. The corpus also contains information about the users' cognitive abilities and detailed usability assessments of each dialogue system. The corpus, which was collected using a Wizard-of-Oz methodology, has been fully transcribed and annotated with dialogue acts and ''I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 70 publications
(89 reference statements)
0
14
0
Order By: Relevance
“…The latter was transcribed and annotated with simple speech acts such as "signaling emotions" or "self-addressing". The MATCH corpus (Georgila et al, 2010) is a small corpus of 447 dialogues based on a Wizard-of-Oz experiment, which contains conversations from 50 young and old adults interacting with spoken dialogue systems. These conversations were annotated semi-automatically with dialogue acts and "Information State Update" (ISU) representations of dialogue context.…”
Section: Othermentioning
confidence: 99%
“…The latter was transcribed and annotated with simple speech acts such as "signaling emotions" or "self-addressing". The MATCH corpus (Georgila et al, 2010) is a small corpus of 447 dialogues based on a Wizard-of-Oz experiment, which contains conversations from 50 young and old adults interacting with spoken dialogue systems. These conversations were annotated semi-automatically with dialogue acts and "Information State Update" (ISU) representations of dialogue context.…”
Section: Othermentioning
confidence: 99%
“…It is difficult to extrapolate from knowledge of cognitive ageing to the usability problems that older users will encounter [14,15], not least because the trajectory of cognitive ageing is incredibly diverse. Existing work includes design patterns [16], databases of interactions between older people and interactive voice response systems [17] and voice interfaces for specific applications (e.g., [10,18,19]). …”
Section: Why Voice Interfaces?mentioning
confidence: 99%
“…Some authors (Baba et al, 2004) have reported that classical ASR systems exhibit poor performances for older adults' voice. The MATCH corpus is a collection of dialogues in which older and younger users interacted with a spoken dialogue system in English (Georgila et al, 2010). Analysis made thanks to the MATCH corpus confirmed that representative corpora of human-machine interactions need to contain a substantial sample of older adults.…”
Section: Asr Performances With Aged Voice and Expressive Speechmentioning
confidence: 99%